Seasonal Changes in the Concentration of Chlorophyll “A” in the Waters of the Siemiatycze Reservoir - Szatyłowicz Ewa; Siemieniuk Anna (Architecture, Civil Engineering, Environment)
The concentration of chlorophyll “a” is an important parameter of water quality, because it characterizes the amount, variety of phytoplankton and algae biomass in the water. Several years of observations, based on its concentration enables to prognosticate algae blooms. It allows taking protective measures of water against the phenomenon of “water blooms”. Therefore this paper assays determination of the seasonal changes in the content of this indicator in the artifical lake waters, which are under the influence of a strong human impact. Included in paper research of sesonal variation of concentrations of chlorophyll “a” in the waters of Siematyczne Reservoir, were systematically pursued in seven measurement-control points in the hydrological year, i.e. November 2021–October 2022. The selection and placement of points in a longitudinal section of the reservoir was based on the need to capture the changes accurring in the studied indicators In addition, in water samples were also detemined: pH, dissolved oxygen concentration and appropriate electrolytic conductivity. During the entire period of the study were observed high variability of the results of the chlorophyll “a” testify aboutits concentration based on the weather conditions, what is associated with seasonality. Criteria of concentration are based on the ranges of concentrations of chlorophyll “a” elaborated by the OECD. Nürnberg, Forsberg and Ryding have defined trophic state of Siemiatycze dam reservoir as eutrophic.